Possibility of separation of elastic and inelastic channels radiation damage metals (International Journal of Mathematics and Physics, 2016)
In this work we have performed a systematical investigation of energy dependence of the radiation defects distribution profile in three different materials – tantalum, molybdenum and stainless steel of type 10Х18Н10Т–VD irradiated by high energy protons. It has been shown that in the stainless steel and tantalum, regardless of proton energy, the vacancy complexes similar by configuration appear which are described by the slightly expressed elastic channel. The defects recover in one annealing stage with different migration activation energy. At the same time the molybdenum radiation damageability consists of two components in each of which exists its own mechanism of defects formation. For high energy protons what’s important is the inelastic channel of interaction and formation of sub cascades, which are created by primarily knocked-on atoms of considerable energies. However, for low energy protons, the processes of elastic interaction with lattice atoms and emergence of atomic hydrogen in the end of run important.   GMT АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский АнглийскийИспанскийИтальянскийКазахскийКитайский ТрадКитайский УпрКорейскийРусскийТурецкийФранцузский        Звуковая функция ограничена 200 символами  Настройки : История : Обратная связь : DonateЗакрыть